2014
DOI: 10.1155/2014/854687
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Tyrosinases: Promising Enzymes for Pharmaceutical, Food Bioprocessing, and Environmental Industry

Abstract: Tyrosinase is a natural enzyme and is often purified to only a low degree and it is involved in a variety of functions which mainly catalyse the o-hydroxylation of monophenols into their corresponding o-diphenols and the oxidation of o-diphenols to o-quinones using molecular oxygen, which then polymerizes to form brown or black pigments. The synthesis of o-diphenols is a potentially valuable catalytic ability and thus tyrosinase has attracted a lot of attention with respect to industrial applications. In envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
111
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(130 citation statements)
references
References 156 publications
2
111
0
6
Order By: Relevance
“…The enzyme also has many applications in food industry. The demand of enzyme has been increased in various industries 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme also has many applications in food industry. The demand of enzyme has been increased in various industries 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Eumelanin is formed through reactions from dihydroxyindole (DHI) and dihydroxyindole-2-carboxylic acid (DHICA) which are the reaction products of DOPA chrome ( Figure 1). Subsequently pheomelanin is formed by the oxidative polymerization of cysteinyl DOPA [9][10][11]. Though there are three enzymes involved in melanogenesis pathway, only tyrosinase is extremely important for melanogenesis, as it plays a key role in the process.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on inhibition and activation of tyrosinase could prove beneficial to agricultural, food, cosmetic, and pharmaceutical industries [1,2]. Studies on synthetic and natural substances with inhibitory potential have resulted in discovery of some strong inhibitors [3,4], as well as an understanding of some structural requirements for tyrosinase inhibition [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, ethyl and propyl xanthate activated cresolase activity at low concentrations (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) µM) but worked as inhibitors at higher concentrations [17]. In a different study, it was shown that some selected α-keto acids activated catecholase activity but worked as inhibitors in cresolase reaction [18].…”
Section: Introductionmentioning
confidence: 99%